Pancasila Sebagai Dasar Hukum Dalam Mewujudkan Keadilan Sosial - Daffa Fittaktahta Putra; Ali Fahmi; Agung Prasetyo; Fandra Firmansyah; Imam Ghozali (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Pancasila as the legal basis for realizing social justice in Indonesia. Pancasila is also the basis of the State in Indonesia, which contains the values ​​of justice, democratic unity and social welfare. Social justice is a fundamental principle in the legal system in Indonesia which aims to create equality, balance and prosperity for all citizens. Pancasila is the basis for the formation of legal regulations oriented towards social justice, as well as how to implement Pancasila values ​​in social and political life in Indonesia. Through legal analysis and literature review, it is hoped that this journal will provide a deeper understanding of the relationship between Pancasila and realizing social justice in the legal context in Indonesia.